Forecasting >300 MeV SEP Events: Extending SPARX to High Energies - C. O. G. Waterfall; S. Dalla; M. S. Marsh; T. Laitinen; A. Hutchinson (Space Weather)
Abstract The forecasting of solar energetic particles (SEPs) is a prominent area of space weather research. Numerous forecasting models exist that predict SEP event properties at proton energies <100 MeV. One of these models is the Solar Particle Radiation SWx (SPARX) system, a physics‐based forecasting tool that calculates >10 and >60 MeV flux profiles within minutes of a flare being detected. This work describes SPARX−H, the extension of SPARX to forecast SEP events above 300 MeV. SPARX−H predicts fluxes in three high energy channels up to several 100 MeV. Correlations between SEP peak flux and peak intensity of the associated solar flare are seen to be weak at high energies, but improved when events are grouped based on the field polarity during the event. Initial results from this new high energy forecasting tool are presented here and the applications of high energy forecasts are discussed. Additionally, the new high energy version of SPARX is tested on a set of historic SEP events. We see that SPARX−H performs best when predicting peak fluxes from events with source locations in well‐connected regions, where many large SEP events tend to originate.